Non-invasive assessment of skeletal muscle fibrosis in mice using nuclear magnetic resonance imaging and ultrasound shear wave elastography - Aurea B. Martins-Bach (Nature Portfolio, 2021)
Abstract Fibrosis is a key pathological feature in muscle disorders, but its quantification mainly relies on histological and biochemical assays. Muscle fibrosis most frequently is entangled with other pathological processes, as cell membrane lesions, inflammation, necrosis, regeneration, or fatty infiltration, making in vivo assessment difficult. Here, we (1) describe a novel mouse model with variable levels of induced skeletal muscle fibrosis displaying minimal inflammation and no fat infiltration, and (2) report how fibrosis affects non-invasive metrics derived from nuclear magnetic resonance (NMR) and ultrasound shear-wave elastography (SWE) associated with a passive biomechanical assay. Our findings show that collagen fraction correlates with multiple non-invasive metrics. Among them, muscle stiffness as measured by SWE, T2, and extracellular volume (ECV) as measured by NMR have the strongest correlations with histology. We also report that combining metrics in a multi-modality index allowed better discrimination between fibrotic and normal skeletal muscles. This study demonstrates that skeletal muscle fibrosis leads to alterations that can be assessed in vivo with multiple imaging parameters. Furthermore, combining NMR and SWE passive biomechanical assay improves the non-invasive evaluation of skeletal muscle fibrosis and may allow disentangling it from co-occurring pathological alterations in more complex scenarios, such as muscular dystrophies.